Prevalence and Determinants of Tuberculosis Mantoux Test on Children Under Five in Banyumas District - Sarwani Sri Rejeki Dwi; Pramatama Mars Wijayanti Siwi; Radi; Solikhah; Dorothy Avila Ell Lady (E3S Web of Conferences)
The incidence of children suffering from Tuberculosis (TB) is increasing. A history of contact between adult TB patients and children is an important factor in the transmission of Tuberculosis to children. This research aims to determine tuberculosis's prevalence and determinants in children under five in household contacts in the Banyumas District, Central Java. The design of this research is quantitative with a cross-sectional approach. The sample of this study was children under 5 years of age (toddlers) in Banyumas Regency (District of South Purwokerto and Sumbang) in whose homes there were positive patient of tuberculosis and were willing to undergo a Mantoux test as many as 48 toddlers. Data collection was carried out using the Mantoux test and questionnaires. Data analysis using univariate, bivariate, and multivariate analysis. The prevalence of Tuberculosis among children under five is 270/1000. The most influential variable on the incidence of tuberculosis is health conditions (lumps in glands) with a p-value of 0.009 OR = 83.204 and sleeping in the same room with TB patients ( p-value of 0.035 OR = 14.246). The results concluded that the risk factor of toddler tuberculosis in Banyumas Regency is health condition (lumps in glands) and sleeping in the same room.